(untitled) (Communications in Computational Physics, 2018)
In the late stage of the mitotic cycle of eukaryotic cells, cytokinesis ensues during which a parent cell replicates its nucleus with the necessary genetical substances (i.e., DNAs and chromosomes) and splits into two similar offspring cells. This mitotic process involves complex chemical, biophysical and mechanical processes whose details are just beginning to be unfolded experimentally. In this paper, we propose a full 3-D hydrodynamical model using a phase field approach to study the cellular morphological change during cytokinesis. In this model, the force along the contracting ring induced by remodeling of actin-myosin filament on cell cortex layer at the division plane of the parent cell during cytokinesis, is approximated using a proxy force anchored on the newly formed nuclei. The symmetric or asymmetric cell division is simulated numerically with the model. Our numerical results show that the location of the division plane and the contracting force along the cytokinetic ring on the division plane are essential for the cell division. In addition, our numerical study also shows that, during cytokinesis, surface tension of the cell membrane also contributes to this process by retaining the morphological integrity of the offspring cells. This model and the accompanying numerical simulation tool provide a solid framework to build upon with more sophisticated whole cell models to probe the cell mitotic process.